2014
DOI: 10.1037/h0100992
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness, mode deactivation, and family therapy: A winning combination for treating adolescents with complex trauma and behavioral problems.

Abstract: Mode Deactivation Therapy (MDT) was conceptualized in recognition that the available therapy approaches were not effective in treating adolescents with behavioral problems and comorbid conditions. By combining unique assessment and process components with the acceptance and mindfulness elements of Acceptance and Commitment Therapy and Dialectical Behavior therapy as well as family systems theory, the MDT methodology was formulated. This study is the most recent in a series that establishes an evidence base of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Mindfulness-based interventions, such as Acceptance and Commitment Therapy (ACT) (A-Tjak et al 2015;Ost 2014), are among those that are rapidly gaining in popularity to help decrease a variety of mental health problems in children and adolescents (Tovote et al 2014;Broderick and Jennings 2012;Cotton et al 2015;Zoogman et al 2015), as well as in children, adolescents and adult survivors of childhood maltreatment (Kimbrough et al 2010;Caldwell and Shaver 2015;Lanktree et al 2012;Mannarino et al 2012). Mindfulness training has been found to help diminish symptoms of depression, anxiety, post-traumatic stress disorder (PTSD), sexual dysfunction and general distress in adult women reporting CSA (Earley et al 2014;Kimbrough et al 2010;Brotto et al 2012) and to reduce behavioural, externalized and internalized problems among youth reporting various types of childhood maltreatment (Swart and Apsche 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness-based interventions, such as Acceptance and Commitment Therapy (ACT) (A-Tjak et al 2015;Ost 2014), are among those that are rapidly gaining in popularity to help decrease a variety of mental health problems in children and adolescents (Tovote et al 2014;Broderick and Jennings 2012;Cotton et al 2015;Zoogman et al 2015), as well as in children, adolescents and adult survivors of childhood maltreatment (Kimbrough et al 2010;Caldwell and Shaver 2015;Lanktree et al 2012;Mannarino et al 2012). Mindfulness training has been found to help diminish symptoms of depression, anxiety, post-traumatic stress disorder (PTSD), sexual dysfunction and general distress in adult women reporting CSA (Earley et al 2014;Kimbrough et al 2010;Brotto et al 2012) and to reduce behavioural, externalized and internalized problems among youth reporting various types of childhood maltreatment (Swart and Apsche 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In seven of the 14 studies, parental involvement was detailed, but only three of these studies reported about the intensity of the involvement (how often parents were seen). Parental involvement was quite low in two and high in one of these studies (Swart & Apsche, 2014a, 2014b, 2014c). In the latter, the adolescent, parent(s), and other family members were offered weekly individual and group therapy (including mindfulness) for 8-12 months, depending on the level of cooperation of the family members.…”
Section: Parental Involvementmentioning
confidence: 90%
“…After all, it is known that many adolescents who end up in forensic care have a troubled history (Dierkhising et al, 2013; Van Grinsven & Holdorp, 2015). In two of the seven included studies that involved parent(s) or guardian(s) in treatment, the adolescents reported to have experienced at least one form of child abuse during their childhood (Swart & Apsche, 2014b, 2014c). It can be assumed that this finding can be applied to a great number of studies.…”
Section: Discussionmentioning
confidence: 99%
“…The MDT research studies also utilized behavioral monitoring, which, although it is a more subjective method with less formalized inter-rater reliability, produces results that are nevertheless qualitatively useful to track potentially harmful behavioral incidents. In terms of aggression, elimination of both physical and sexual posttreatment incidents were above 90%, [32][33][34] with follow-up results at up to 18months even better. Similarly, in the suicidal and parasuicidal group, self-harm incidents were reduced by more than 95% after treatment.…”
Section: Mdt Effectivenessmentioning
confidence: 91%